Deepfake Pornography: How Criminal Liability of Perpetrators in the Indonesian Criminal Law Framework - Fuadi Isnawan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
his study explores the issue of criminal liability for the distribution of deepfake pornography in Indonesia, an emerging form of cybercrime that leverages artificial intelligence (AI) technologies, particularly Generative Adversarial Networks (GANs), to create nonconsensual hyper-realistic sexual content. The research highlights the legal, social, and ethical implications of deepfake pornography, which disproportionately targets women and perpetuates gender-based violence. Despite the growing prevalence of such content, Indonesian legal frameworks currently provide limited protection for victims of deepfake pornography. This normative legal research examines the applicability of two primary legislative tools: The Information and Electronic Transactions Act (ITE Law), Law Number 27 2022 (PDP Law) and the Pornography Law. The ITE Law, while not explicitly mentioning pornography, addresses content that violates decency, including deepfake pornography. In PDP Law which offer crucial legal protections against the unlawful processing of personal data, including the manipulation of individuals’ likenesses in deepfake content. Article 66 outlines the legal recourse available for victims whose personal data, such as their image, has been altered or disseminated without consent. Meanwhile, Article 68 establishes penalties for violations of data processing, further strengthening criminal accountability in cases involving deepfake pornography. The Pornography Law specifically prohibits the creation and dissemination of nonconsensual pornographic material, covering digitally manipulated content. The findings underscore the importance of mens rea (intent) and actus reus (criminal actions) in establishing criminal liability for deepfake pornography perpetrators under Indonesian law. In conclusion, the research calls for more comprehensive legal reforms to better protect victims of this evolving cybercrime, emphasizing the need to adapt to technological advancements while upholding privacy and dignity. elitian ini mengeksplorasi isu pertanggungjawaban pidana atas distribusi pornografi deepfake di Indonesia, sebuah bentuk kejahatan siber yang sedang berkembang yang memanfaatkan teknologi kecerdasan buatan (artificial intelligence/AI), khususnya Generative Adversarial Networks (GAN), untuk membuat konten seksual hiper-realistis yang tidak konsensual. Penelitian ini menyoroti implikasi hukum, sosial, dan etika dari pornografi deepfake, yang secara tidak proporsional menargetkan perempuan dan melanggengkan kekerasan berbasis gender. Terlepas dari meningkatnya prevalensi konten semacam itu, kerangka hukum Indonesia saat ini hanya memberikan perlindungan yang terbatas bagi para korban pornografi deepfake. Penelitian hukum normatif ini mengkaji penerapan dua perangkat legislatif utama: Undang-Undang Informasi dan Transaksi Elektronik (UU ITE), Undang-Undang Nomor 27 Tahun 2022 (UU PDP), dan Undang-Undang Pornografi. UU ITE, meskipun tidak secara eksplisit menyebutkan pornografi, membahas konten yang melanggar kesusilaan, termasuk pornografi deepfake. Dalam UU PDP yang menawarkan perlindungan hukum yang penting terhadap pemrosesan data pribadi yang melanggar hukum, termasuk manipulasi kemiripan individu dalam konten deepfake. Pasal 66 menguraikan jalur hukum yang tersedia bagi para korban yang data pribadinya, seperti gambarnya, telah diubah atau disebarkan tanpa persetujuan. Sementara itu, Pasal 68 menetapkan hukuman untuk pelanggaran pengolahan data, yang semakin memperkuat akuntabilitas pidana dalam kasus-kasus yang melibatkan pornografi deepfake. UU Pornografi secara khusus melarang pembuatan dan penyebaran materi pornografi yang tidak sesuai dengan persetujuan, termasuk konten yang dimanipulasi secara digital. Temuan ini menggarisbawahi pentingnya mens rea (niat) dan actus reus (tindakan kriminal) dalam menetapkan pertanggungjawaban pidana bagi pelaku pornografi deepfake di bawah hukum Indonesia. Sebagai kesimpulan, penelitian ini menyerukan reformasi hukum yang lebih komprehensif untuk melindungi korban kejahatan siber yang terus berkembang ini, dengan menekankan perlunya beradaptasi dengan kemajuan teknologi dengan tetap menjunjung tinggi privasi dan martabat.